Perancangan Website Sebagai Media Pemasaran Produk UMKM - Billah, Muktashim; Razi A, Muhammad; dkk, Ayu Indryani (Jurnal Sistem Informasi Dan Informatika, 2023)
The development of information and communication technology is currently taking place very rapidly. This is inseparable from the existence of the internet as one of the communication media and information providers in various circles, including for MSME actors. MSME stands for Micro, Small, and Medium Enterprises. Basically, MSMEs are the meaning of businesses or businesses carried out by individuals, groups, small business entities, and households. Indonesia as a developing country makes MSMEs the main foundation of the community's economic sector, this is done to encourage the ability of independence in developing in the community, especially in the economic sector. The development of MSMEs in Indonesia continues to increase, this is due to strong support from the government in the development carried out for MSME business activists, which is very important in anticipating future economic conditions as well as maintaining and strengthening the national economic structure. Behind all that, to be able to develop MSME actors must be able to market their products so that they can be known to the wider community by utilizing technology.